Factors Associated With The Incidence Of Diarrhea In ToddlersIn The Meureubo Health Center Working Area, Meureubo Sub-District, West Aceh District In 2023 - Fassa, Muhammad; Amin , Fauzi Ali; Arbi , Anwar; Khairuman, Khairuman (Maneggio, 2024)
Diarrhea in children under five is a significant public health problem, especially in developing countries, where the incidence and mortality rate due to diarrhea is still high. This phenomenon is further exacerbated by the lack of access to proper sanitation and health education among the community. This study aims to identify factors related to the incidence of diarrhea in toddlers in the working area of the Meureubo Health Center, Meureubo District, West Aceh Regency, in 2023. The method used is a literature study, with data and information obtained from various sources, including scientific journals, articles, and related reports. The analysis was carried out on factors that affect the incidence of diarrhea, such as environmental sanitation, diet, immunization status, and parental knowledge about health and diarrhea prevention. Although there has been previous research on diarrhoea in toddlers, there is still a lack of understanding the specific association between parental knowledge and the incidence of diarrhoea in this local context. The results of the study showed that drinking water quality, hygiene practices, and parental knowledge about diarrhea prevention had a significant influence on the incidence of diarrhea in toddlers. These findings emphasize the need for health interventions that focus on improving access to clean water, good sanitation, and education for parents. This research is expected to provide useful information for the development of more effective health intervention programs in the region as well as increase public awareness about the importance of diarrhoea prevention among toddlers.